The Effect of Addition of Mangrove Avicennia Marina Extract on The Biofouling Activity to Epoxy Coating - Aisyah, Dwi Maharani; Pratikno, Herman; Titah, Harmin Sulistiyaning (International Journal of Offshore and Coastal Engineering (IJOCE), 2022)
Biofouling is one of the problems related to construction maintenance in industrial developments in the maritime construction sector because biofouling adhesion can affect construction productivity. This problem can be overcome by coating using natural-based paints to reduce the ecological impact that will occur. This study aims to determine the effect of the addition of Avicennia marina mangrove extract as an anti-fouling compound mixed with epoxy paint. This research was conducted by mixing Avicennia marina mangrove extract with epoxy paint. Then the alloy is applied as a coating on the ASTM A36 steel specimen. Furthermore, the test was carried out by immersing the specimen in a solution containing Littorina littorea as a biofouling biota. The average results of the biofouling affixing activity test with the addition of mangrove extract concentrations of 0%, 10%, 20%, and 30% were respectively 24.0 gr, 20.5 gr, 13.5 gr, and 6 gr. This test shows that the more the addition of mangrove extracts, the smaller the adhering activity of biofouling to the specimen.